Older Primary Care Patients’ Willingness to Consider Discontinuation of Chronic Benzodiazepines - Cook, Joan M. (2007)
OBJECTIVE: To examine factors related to older primary care patients’ willingness to consider tapering/discontinuation of long-term benzodiazepine use. METHOD: Forty-six long-term anxiolytic benzodiazepine users, aged 61-95 years, were assessed over the telephone using a semi-structured qualitative interview and standardized self-report questionnaires for anxiety (Beck Anxiety Inventory), sleep quality (Pittsburgh Sleep Quality Index), depression (Center for Epidemiological Studies Depression Scale), psychological dependence on benzodiazepines (Severity of Dependence Scale) and anxiety sensitivity (Anxiety Sensitivity Index). RESULTS: Frequency of daily benzodiazepine intake and anxiety sensitivity significantly contributed to willingness to attempt taper/discontinue benzodiazepines. CONCLUSION: Many older long-term benzodiazepine users and their physicians perceive tapering of use an arduous, low priority, time intensive task. These findings highlight factors that can help identify a subpopulation of patients who may be easier to engage in the discontinuation process.